THE IMPLEMENTATION OF JAKARTA ENTREPRENEURSHIP (JAKPRENEUR) PROGRAM IN EMPOWERING SMALL AND MEDIUM ENTERPRISES IN KEMBANGAN DISTRICT ADMINISTRATIVE CITY OF WEST JAKARTA - Anna Elisabeth Panjaitan; Arifiani Widjayanti; Edy Sutrisno (Journal of Business Administration Economics & Entrepreneurship, 2022)
Currently the civilization of human life in the world is changing very quickly and unexpectedly. Coupled with the Covid-19 Pandemic, that has completely changed the design of human life, it becomes more instability and uncertainty in all social life. As a result, uncertain economic conditions emerge, conditions that can change at any time, which causes the business world to be forced to change quickly to keep up with it.SMEs have always been proven to be able to survive in crisis. Even now, SMEs are one of the sectors that are relied upon in supporting the national economic recovery due to the Covid-19 pandemic. Therefore, it is very impossible if the Government ignores the importance of human resources development, especially MSME actors. SMEs are required to be able to work on market opportunities in domestic and international markets and be able to compete with other nations. This real phenomenon is an interesting thing to study, namely how the role of digital transformation in strengthening the ecosystem of SMEs actors so that they can optimally utilize digital facilities in the promotion of business products and even in the process of trade transactions.Right regulation of SMEs Development Policy is very much needed for SMEs at this time. Reformation is needed in SMEs development governance for service-oriented and cross-sectoral policies. For this reason, Jakpreneur is here to help provide solutions for these SMEs with development programs for skills and business independence. Jakpreneur is a collaboration between the DKI Jakarta Provincial Government, education actors,SMEs stakeholders and the people of DKI Jakarta.This research applies case studies with descriptive qualitative methods, which examines and reviews the optimization of digital literacy for SMEs actors of Jakpreneur program in West Jakarta PPKUKM Sub-department, especially the Kembangan District Unit, in order to enable it to adapt to this completely uncertain situation, and be able to remain stable and even more advanced in business, which finally can bolster the economic recovery.The results of the study show the lack of awareness of business actors about business legality, understanding of the importance of having a personal business license, formally named as Business Permit Numbers (NIB). There are also many SMEs actors who have not been able to show their potential and identity optimally, because they are still confined by structural, cultural, and their natural limitations/poverty.Socialization and collaboration are important keys that are expected to help educate the public about the importance of the program for business development, when now this socialization effort is still not massive enough to reach the MSMEs actors. Trainings or workshops given to participants which still general and theoretical, need to be equipped with hands-on practice on product development innovation techniques, and of course practical matters related to digital ecosystem support so that they can be implemented more intensely and in depth.Keyword : Empowering, Small Medium Entreprises, Public Service, Jakpreneur